Adherence to lipid-lowering therapy and risk for cardiovascular disease and death in type 1 diabetes mellitus: a population-based study from the Swedish National Diabetes Register. Issue 1 (13th January 2020) - Hero, Christel; Karlsson, Sofia Axia; Franzén, Stefan; Svensson, Ann-Marie; Miftaraj, Mervete; Gudbjörnsdottir, Soffia; Andersson Sundell, Karolina; Eliasson, Björn; Eeg-Olofsson, Katarina
Abstract : Aims/hypothesis: Dyslipidemia is an important modifiable risk factor and lipid-lowering treatment (LLT) is essential to reduce the risk of cardiovascular disease (CVD). Studies in type 2 diabetes indicate that low adherence to statin therapy is a barrier to reach full protective potential, and less is known in type 1 diabetes (T1D). The aim was to assess risk of CVD by adherence and nonpersistence to LLT in T1D.  Method: A population-based study with a retrospective longitudinal design was conducted between 2006 and 2010, with follow-up until December 2013. In total, 6192 adult individuals with T1D, initiating LLT between 2006 and 2010, were included. Information on LLT, socioeconomic characteristics, comorbidities and cardiovascular events were collected. After 18 months, refill adherence was estimated by calculating medication possession ratio (MPR). Nonpersistence was defined as being without medicines on hand for at least 180 days. Individuals were thereafter followed until CVD, death or end of follow-up in December 2013. Cox regression analyses were performed to assess adherence level and nonpersistence of LLT as predictor of CVD. Analyses were adjusted for cardiovascular risk factors and socioeconomic status.   Results: Mean MPR was 72%, 52% of the participants had an MPR above 80% and 27% discontinued LLT. There were 637 nonfatal and 58 fatal CVD events, mean follow-up 3.6 and 3.9 years, respectively. MPR above 80% was associated with reduced risk for nonfatal CVD compared with lower MPR, HR 0.78 (95% CI 0.65 to 0.93)). For fatal CVD, results indicated a negative effect of high adherence but the association did not reach statistical significance, HR 1.96 (0.96 to 4.01). Individuals discontinuing LLT had higher risk of nonfatal CVD, HR 1.43 (95% CI 1.18 to 1.73).  Conclusions/Interpretation: In T1D, the risk for nonfatal CVD was lower among individuals with high adherence and higher among those discontinuing LLT within 18 months. It is important to evaluate and emphasize adherence to prescribed LLT at clinical visits to achieve treatment goals and reduce the risk of CVD.